2011
DOI: 10.1074/jbc.m111.256248
|View full text |Cite
|
Sign up to set email alerts
|

Premature Activation of the Paramyxovirus Fusion Protein before Target Cell Attachment with Corruption of the Viral Fusion Machinery

Abstract: Paramyxoviruses, including the childhood pathogen human parainfluenza virus type 3, enter host cells by fusion of the viral and target cell membranes. This fusion results from the concerted action of its two envelope glycoproteins, the hemagglutinin-neuraminidase (HN) and the fusion protein (F). The receptor-bound HN triggers F to undergo conformational changes that render it competent to mediate fusion of the viral and cellular membranes. We proposed that, if the fusion process could be activated prematurely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 58 publications
(58 reference statements)
4
64
0
Order By: Relevance
“…6 and 7), indicating that F has the ability to progress spontaneously. We also have found that, in the absence of HN, processed F is sensitive to proteolysis (18). Taken together, these data suggest that HN protects processed F from untimely activation (18,37), and only when it is receptor engaged does it proceed to activate F.…”
Section: Discussionsupporting
confidence: 49%
“…6 and 7), indicating that F has the ability to progress spontaneously. We also have found that, in the absence of HN, processed F is sensitive to proteolysis (18). Taken together, these data suggest that HN protects processed F from untimely activation (18,37), and only when it is receptor engaged does it proceed to activate F.…”
Section: Discussionsupporting
confidence: 49%
“…While the stalk domain is a major determinant for specific F activation, we propose that the globular head can be interchangeable and that the repressive role, if present, is due to the stalk domain. For HPIV3, HN not only specifically activates fusion after receptor engagement but also prevents premature activation of F before receptor engagement (57), and the stalk domain is responsible for the stabilization effect. The stability of the F protein in the absence of receptor protein may be different for each virus in the family and may be the product of adaptation of the viruses to specific hosts or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact nature of these rearrangements and that of the F-HN/H/G interaction are not well understood. Multiple studies have shown that retargeted MeV H or NDV HN heads binding noncognate receptors are able to trigger F (45)(46)(47)(48)(49) and chimeric attachment proteins bearing globular heads or stalks from different viruses in various combinations are functional when paired with the cognate F protein corresponding to the stalk domain portion of the chimeric attachment protein (31,42,(49)(50)(51)(52)(53). Recent data have also shown that "headless" PIV5 HN, MeV H, and NiV G proteins, lacking the globular head domains in their entirety, are sufficient to trigger their cognate F proteins (42,54,55).…”
Section: Paramyxoviruses Are a Large Family Of Membrane-enveloped Negmentioning
confidence: 99%